Epifania podlaska. Spotkanie z białoruskim Innym i rekonstrukcja tożsamości w Sońce (2014) i Miłości (2017) Ignacego Karpowicza Akcja - Ghilarducci, Manuel (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article, by means of an analysis of the role of visual and linguistic epiphany in the novels Sońka (2014) and Love (Miłość) (2017), based on the philosophy of Martin Heidegger, Jacques Lacan and Emmanuel Lévinas, aims to expand the existing research on Ignacy Karpowicz’s geopoetics and literary provincialism.